Pengaruh Harga dan Metode Pembayaran COD Terhadap Minat Beli Produk Skincare di E-commerce Shopee - Simanjuntak, Anisa; Katerina, Angel (Universitas Malahayati, 2024)
This study aims to determine the effect of price and the Cash On Delivery (COD) payment method on buying interest in Skincaredi products in Shopee e-commerce. The data used in this study are primary data. The population in this study were Shopee e-commerce consumers. The sample used was 111 respondents. The sampling technique is non-probability sampling and purposive sampling method. Primary data in this study were obtained from a questionnaire. The data analysis techniques used are validity test, reliability test, classical assumption test consisting of normality test, multicolonierity test, and heteroscedasticity test, multiple linear regression analysis, hypothesis testing consisting of t, f and coefficient of determination tests. The results in this study indicate that the price and COD payment method have a positive and significant effect on buying interest simultaneously.